Calibration of CVD-diamond based dosimeter in high-power electron and X-ray radiation fields - Kutny, V.E.; Nikiforov, V.I.; Opalev, O.A.; Rogov, Yu.V.; Rybka, A.V.; Shevchenko, V.A.; Shlyakhov, I.N.; Strelnitsky, V.E.; Tenishev, A.Eh.; Uvarov, V.L. (Вопросы атомной науки и техники, 2014)
Results of a study of dosimetry characteristics of a prototype of the detector based on a polycrystalline diamond
film (CVD-diamond) produced in NSC KIPT are summarized. The techniques of the detector calibration against the
electron and X-ray radiation dose rate are developed. The conditions of calibration were studied by means of computer
simulation. For determination of detector sensitivity to electron radiation, it was placed inside of a standard
polystyrene phantom. An additional filter of electrons was used at measurement in the X-ray field. Every time detector
irradiation was carried out together with the Harwell Red Perpex 4034 dosimeters, which registrations provided
the calibration data. The measurements, executed at the LU-10, EPOS and LU-40 linacs of NSC KIPT, have demonstrated,
that the values of detector sensitivity against each type of radiation are close and conform to ones obtained
earlier for the low-intensity radiation fields. Considering significant radiation durability of the CVD-diamond, it
enables its application in technological dosimetry. Описаны результаты исследования дозиметрических характеристик изготовленного в ННЦ ХФТИ опытного образца детектора на основе поликристаллической алмазной пленки (CVD-алмаз). Разработаны методики калибровки детекторов по мощности поглощенной дозы электронного и тормозного излучений. Условия калибровки исследованы методом компьютерного моделирования. Для определения чувствительности детектора к электронному излучению его помещали внутри фантома из полистирола. При измерениях в поле тормозного излучения использовался дополнительный фильтр электронов. В каждом случае облучение детектора выполнялось совместно с дозиметрами Harwell Red Perspex 4034, по показаниям которых производилась калибровка. Проведенные на ускорителях ЛУ-10, ЭПОС и ЛУ-40 ННЦ ХФТИ измерения показали, что значения чувствительности детектора для каждого вида излучения близки и согласуются с полученными ранее в условиях полей излучения низкой интенсивности. Учитывая высокую радиационную стойкость CVD-алмаза, это обеспечивает возможность его применения в технологической дозиметрии. Описанo результати дослідження дозиметричних характеристик виготовленого в ННЦ ХФТІ дослідного зразка детектора на основі полікристалічної алмазної плівки (CVD-алмаз). Розроблено методики калібрування детекторів за потужністю поглинутої дози електронного та гальмівного випромінювань. Методом комп'ютерного моделювання досліджені умови калібрувань. Для визначення чутливості детектора до електронного випромінювання його розміщували усередині стандартного фантома з полістиролу. При вимірюваннях у полі гальмівного випромінювання використовувався додатковий фільтр електронів. У кожному випадку опромінювання детектора виконувалося спільно з дозиметрами Harwell Red Perpex 4034, за показаннями яких проводилося калібрування. Проведені на прискорювачах ЛУ-10, ЕПОС та ЛУ-40 ННЦ ХФТІ вимірювання показали, що значення чутливості детектора для кожного виду випромінювання є близькі і узгоджуються з такими, що одержані раніше в умовах полів випромінювання низької інтенсивності. Зважаючи на значну радіаційну стійкість CVD-алмазу, це забезпечує можливість його застосування в технологічній дозиметрії.